Paul Zenon's Practical Jokes: Pranks, Wind-Ups And Tricks - Paul Zenon
There's nothing more fun than fooling your family and friends! And these good-natured but sly tricks, all fully illustrated and presented in Paul Zenon's inimitable style, will get 'em every time. Zenon dishes "The Dirt" on how to make each joke work, with an explanation of what it entails and why to do it, as well as a full explanation of the necessary setups for success.